Operationalizing distributive justice from the perspective of Islamic economics - Rahim, Shafinah; Mohamed, Mustafa Omar (IIUM Press, 2018)
The idea of distributive justice is an important subject matter immensely debated in studies of philosophy, political, behavioral and social sciences; it has yet to be thoroughly analyzed in economics. Despite its relevance, works in the formulation of models of distributive justice in Islamic Economics are lacking relative to those available in Western scholarship. The existing scholarly products deal mainly with limited applied aspects of distributive justice. Alternatively, the current conceptual paper is an inaugural analysis of the notion of distributive justice from the sources of Islamic heritage (Turath). The effort is aimed at guiding practitioners and policymakers to find solutions to economic distributional problems in the Muslim world in particular. This research attempts to critically review accessible Islamic Economic literature written on distributive justice and propose a model of distributive justice using the operationalization method introduced by Sekaran and Bougie (2010). It begins with a brief survey of related works by exploring justice and distribution separately. Next the concept of distributive justice is translated into principles and observable dimensions found in the sources of revealed knowledge. Lastly the findings are presented in the form of the proposed model of distributive justice based solely on evidence in the Holy Qurʾān and Ḥadīth. Recommendations are made for expanding the model to fit the special needs of different Islamic economies battling severe distributive injustices stemming from the reliance on conventional theories. Empirical analysis to further defend the viability of the proposed model of distributive justice is highly valued.